The practical aspect of using the artificial intellectual technology for building a multidimentional function CFAR for smart-handled LPI radar - Kosovets, M.; Tovstenko, L. (Проблеми програмування, 2020)
The problem of the development of modern mobile smart-handled LPI radars using artificial intelligence technologies, the main difference of which is the construction of the CFAR function, which takes into account the influence of external and internal factors and requirements for the purpose, also distinguishes the developed radar among others in its class. The analysis of the publications was showed a great interest in modern radar systems and the lack of a unified approach to solving this problem. The purpose of the article is to reduce this gap, from collecting information from radar sensors and internal sensors to construct a generic multidimensional CFAR function and for organize its effect on the receiving and transmitting part of the radar. The application of artificial intelligence technologies in the construction of a modeling complex of LPI radars with CFAR function and their debugging in real time is covered Рассмотрена проблема разработки современных мобильных интеллектуальных LPI радаров, используя технологии искусственного интеллекта, основное отличие которых заключается в построении функции CFAR, учитывающий влияние внешних и внутренних факторов и требования по назначению, также она отличает разрабатываемый радар среди других в своём классе. Проведённый анализ публикаций показал большую заинтересованность современными радарными системами и отсутствие единого подхода к разрешению этой проблемы. Цель статьи - уменьшить этот пробел, начиная по сбору информации от радарных сенсоров и внутренних датчиков для построения обобщающей многомерной функции CFAR и организации её влияния на приёмную и передающую часть радара. Освещены применения технологий искусственного интеллекта при построении моделирующего комплекса LPI радаров с функцией CFAR и их отладки в реальном масштабе времени. Розглянуто проблему розробки сучасних мобільних інтелектуальних LPI радарів використовуючи технології штучного інтелекту, основна відмінність яких полягає в побудові функції CFAR, що враховує вплив зовнішніх та внутрішніх факторів і вимоги по призначенню, також вона вирізняє розроблюваний радар серед інших у своєму класі. Проведений аналіз публікацій показав велику зацікавленість сучасними радарними системами і відсутність єдиного підходу до розв’язання цієї проблеми. Мета статті – зменшити цю прогалину, починаючи зі збору інформації від радарних сенсорів та внутрішніх датчиків для побудови узагальнюючої багатовимірної функції CFAR та організації її впливу на приймальну і передавальну частину радару. Висвітлено застосування технологій штучного інтелекту при побудові моделюючого комплексу LPI радарів з функцією CFAR та їх відлагодження в реальному масштабі часу.